Translational Physiologically Based Pharmacokinetic Modeling to Predict Human Pulmonary Kinetics After Lung Delivery - Haini Wen; Muhammad Waqas Sadiq; Lena E. Friberg; Elin M. Svensson (CPT: Pharmacometrics & Systems Pharmacology)
ABSTRACT Predicting human lung exposure with reasonable certainty of orally inhaled drugs based on preclinical studies remains a challenge for drug development. We have developed a comprehensive physiologically based pharmacokinetic (PBPK) framework tailored for the pulmonary pharmacokinetic (PK) behavior in both humans and rats, aiming to bridge the translational gap. In this study, we present a mechanistic pulmonary PBPK model for rats that integrates the pulmonary disposition processes, including drug deposition, dissolution, mucociliary clearance, and mass transfer in lung tissues. Apparent permeabilities were translated to effective permeabilities (Peff) with in vivo–in vitro correlation methods. Unbound tissue–plasma partition coefficients for lung (Kp,u,lung) and Peff were estimated with plasma and lung PK profiles of salbutamol and fluticasone propionate in rats. The developed PBPK model was translated by keeping the estimated parameters and switching physiological and anatomical parameters from rats to humans. Based on PK observations in rats, the estimated typical Peff and Kp,u,lung for salbutamol were 1.18 × 10−5 cm/s and 8.83 and for fluticasone propionate 1.26 × 10−4 cm/s and 1086, respectively. After interspecies translation, the model framework well predicted the mean epithelial lining fluid concentrations following oral inhalation of salbutamol and fluticasone propionate in human subjects, with fold‐errors of lung‐to‐plasma ratios < 2. Thus, the proposed general pulmonary PBPK framework exhibits the potential to facilitate interspecies translation and can be used to predict safety and efficacy of lung‐delivered therapeutics in human.